2012
DOI: 10.1098/rstb.2011.0268
|View full text |Cite
|
Sign up to set email alerts
|

The political left rolls with the good and the political right confronts the bad: connecting physiology and cognition to preferences

Abstract: We report evidence that individual-level variation in people's physiological and attentional responses to aversive and appetitive stimuli are correlated with broad political orientations. Specifically, we find that greater orientation to aversive stimuli tends to be associated with right-of-centre and greater orientation to appetitive (pleasing) stimuli with left-of-centre political inclinations. These findings are consistent with recent evidence that political views are connected to physiological predispositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
215
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(222 citation statements)
references
References 49 publications
4
215
2
1
Order By: Relevance
“…Libert/Unaff ---------------------------------------------.77 -.31 1.84 .16 Dodd et al, 2012), summarized by first principal component; see SOM for details.…”
Section: Categorymentioning
confidence: 99%
“…Libert/Unaff ---------------------------------------------.77 -.31 1.84 .16 Dodd et al, 2012), summarized by first principal component; see SOM for details.…”
Section: Categorymentioning
confidence: 99%
“…But differences amongst us arise as to whether it is most important to seek the good or avoid the bad-leading to political differences causing conflicts both within and between cultures-. The definition of politics refers to governing institutions and policies and it is argued that ever since the French Revolution it is common to divide secular political camps into "left" and "right" (Dodd et al 2012). And new physiological evidence, it is argued, shows that there is a biological explanation for this division as they have found two contrasting types of politically relevant variation in cognitive and social dispositions.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…I wonder how-if at allBorrelli, Nomura, and Mandela would have changed their intervention strategies if they had known these research findings. Dodd et al (2012) have not referenced any analysis of specific cultural, political, economic, and social facts of the past, present or the future and considered how these facts might have influenced the mentality of differing categories of people in these contexts or any other context. Their findings seem to be at the level of the "cosmic will", to use Nomura's concept and rooted in the unchangeable part of our sub-conscious.…”
Section: Concluding Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study 10 , Hibbing showed subjects a series of emotionally charged images, including a spider on a man's face, a maggot-infested wound, a cute rabbit and a happy child. People who described themselves as conservatives tended to respond more strongly when looking at the negative images than at the positive images, whereas liberals reacted more to the positive pictures.…”
Section: Visceral Reactionsmentioning
confidence: 99%